Effects of a cognitive-based intervention program using social robot PIO on cognitive function, depression, loneliness, and quality of life of older adults living alone - Lim, JunSeo (Frontiers in Public Health, 2023)
Objective Social robot interventions are being implemented to reduce cognitive decline, depression, and loneliness among older adults. However, the types, functions, and programs of effective social robots have not yet been confirmed. This study investigated whether a social robot intervention is effective in improving cognitive function, depression, loneliness, and quality of life in older adults living alone. Methods This study used a non-equivalent control group pre-test–post-test design. It was conducted twice a week, with each session lasting 50 mi; twelve sessions were conducted over 6 weeks. This study was conducted at three senior welfare centers in Korea. In each group, 10 or fewer participants used the PIO social robot. The total participants included 64 people in the experimental (n = 31) and control groups (n = 33), and consisted of older people over 65 years of age living alone. Results There was a statistically significant difference in the pre-post values for cognitive function (z = 5.21, p < 0.001), depression (z = −2.99, p = 0.003), and loneliness (t = −4.27, p < 0.001) in the experimental and control groups. However, there was no statistically significant difference for quality of life (z = 1.84, p = 0.066). Conclusions It was confirmed that a cognitive intervention program using the social robot PIO can improve cognitive function and reduce depression and loneliness in older adults living alone.